1996
DOI: 10.1007/s002850050040
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric bifurcations for a model in epidemiology

Abstract: In the present paper we make a bifurcation analysis of an SIRS epidemiological model depending on all parameters. In particular we are interested in codimension-2 bifurcations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 5 publications
0
31
0
Order By: Relevance
“…Early work on studying the dynamics of epidemic models focused on Hopf bifurcation, homoclinic bifurcation, or saddle-node bifurcation separately by using only one bifurcation parameter (Derrick and van den Driessche [6], Hethcote and van den Driessche [14], Liu et al [17,18]). Recent studies indicate that some epidemic models undergo codimension 2 bifurcations near degenerate equilibria; i.e., a Bogdanov-Takens bifurcation, which includes a Hopf bifurcation, a homocline bifurcation and a saddle-node bifurcation, can occur when two parameters vary near their critical values (Lizana and Rivero [19], Ruan and Wang [25], Alexander and Moghadas [1,2], Moghadas [21], Wang [26]). It is interesting to notice that not only epidemic models with nonlinear incidence rates but also simple epidemic models with bilinear mass-action incidence rates can have complex dynamics such as the occurrence of Bogdanov-Takens bifurcations.…”
Section: Degenerate Bogdanov-takens Bifurcation By Lemma 23 Whenmentioning
confidence: 99%
See 1 more Smart Citation
“…Early work on studying the dynamics of epidemic models focused on Hopf bifurcation, homoclinic bifurcation, or saddle-node bifurcation separately by using only one bifurcation parameter (Derrick and van den Driessche [6], Hethcote and van den Driessche [14], Liu et al [17,18]). Recent studies indicate that some epidemic models undergo codimension 2 bifurcations near degenerate equilibria; i.e., a Bogdanov-Takens bifurcation, which includes a Hopf bifurcation, a homocline bifurcation and a saddle-node bifurcation, can occur when two parameters vary near their critical values (Lizana and Rivero [19], Ruan and Wang [25], Alexander and Moghadas [1,2], Moghadas [21], Wang [26]). It is interesting to notice that not only epidemic models with nonlinear incidence rates but also simple epidemic models with bilinear mass-action incidence rates can have complex dynamics such as the occurrence of Bogdanov-Takens bifurcations.…”
Section: Degenerate Bogdanov-takens Bifurcation By Lemma 23 Whenmentioning
confidence: 99%
“…It is very important to understand such epidemic patterns in order to introduce public health interventions and control the spread of diseases. Recent studies have demonstrated that the incidence rate plays a crucial role in producing periodic oscillations in epidemic models (Alexander and Moghadas [1,2], Derrick and van den Driessche [6], Hethcote and van den Driessche [14], Liu et al [17,18], Lizana and Rivero [19], Moghadas [21], Moghadas and Alexander [22], Ruan and Wang [25], Wang [26]). …”
mentioning
confidence: 99%
“…The horizontal transmission is assumed to take the form of direct contact between infectious and susceptible hosts. The incidence rate term H(I, S) is assumed to be differentiable, ∂H/∂I and ∂H/∂S are nonnegative and finite for all I and S. For special forms of the incidence rate H(I, S), see [3,10,11,13,14,16]. Here, b is the natural birth rate of the host population which is assumed to have a constant density 1.…”
Section: (T) E(t) I(t) and R(t)mentioning
confidence: 99%
“…In some SIR type models, the incidence rate is bilinear in the infective fraction I and the susceptible fraction S, i.e., the form of κ I S, e.g., [4][5][6]. Recently, many researchers, e.g., [7][8][9][10], pay attention to a nonlinear incidence rate of the form κ I p S q for two reasons: the corresponding models have a much wider range of dynamical behaviors; and the underlying assumption of homogeneous mixing in bilinear rate models may be invalid. More related results are also surveyed, e.g., in [7] or [11].…”
Section: Introductionmentioning
confidence: 99%